Hospitalization rates for pneumococcal disease in Brazil, 2004 - 2006 Hospitalizaciones por enfermedad neumocócica en Brasil, 2004-2006 Hospitalizações por doença pneumocócica no Brasil, 2004 - 2006 - Hillegonda Maria Dutilh Novaes; Ana Marli Christovam Sartori; Patricia Coelho de Soárez (Universidade de São Paulo, 2011)
OBJECTIVE: To estimate hospitalization rates for pneumococcal disease based on the Brazilian Hospital Information System (SIH). METHODS: Descriptive study based on the Hospital Information System of Brazilian National Health System data from January 2004 to December 2006: number of hospitalizations and deaths for pneumococcal meningitis, pneumococcal sepsis, pneumococcal pneumonia and Streptococcus pneumoniae as the cause of diseases reported in Brazil. Data from the 2003 Brazilian National Household Survey were used to estimate events in the private sector. Pneumococcal meningitis cases and deaths reported to the Notifiable Diseases Information System during the study period were also analyzed. RESULTS: Pneumococcal disease accounted for 34,217 hospitalizations in the Brazilian National Health System (0.1% of all hospitalizations in the public sector). Pneumococcal pneumonia accounted for 64.8% of these hospitalizations. The age distribution of the estimated hospitalization rates for pneumococcal disease showed a "U"-shape curve with the highest rates seen in children under one (110 to 136.9 per 100,000 children annually). The highest hospital case-fatality rates were seen among the elderly, and for sepsis and meningitis. CONCLUSIONS: PD is a major public health problem in Brazil. The analysis based on the SIH can provide an important input to pneumococcal disease surveillance and the impact assessment of immunization programs. OBJETIVO: Estimar las hospitalizaciones por enfermedad neumocócica con base en datos del Sistema de Informaciones Hospitalarias (SIH). MÉTODOS: Estudio descriptivo con base en datos del SIH de enero de 2004 a diciembre de 2006: números de hospitalizaciones y muertes por meningitis neumocócica, sepsis neumocócica, neumonía neumocócica y Streptococcus pneumoniae como causa de enfermedades ocurridas en Brasil. Datos de la Investigación Nacional por Muestras de Domicilios 2003 fueron utilizados para el sector privado. Casos y muertes por meningitis neumocócica notificados en el Sistema Nacional de Agravios de Notificación en el mismo período también fueron analizados. RESULTADOS: La enfermedad neumocócica fue responsable por 34.217 hospitalizaciones en el Sistema Único de Salud, (0,1% de todas las hospitalizaciones). Neumonía neumocócica fue responsable por 64,8% de tales hospitalizaciones. La distribución de las estimaciones de hospitalizaciones según grupo etáreo mostró curva en "U", con mayor frecuencia entre niños < 1 año (110-136,9/100.000 niños/año). La letalidad hospitalaria fue más alta entre ancianos, y entre casos de meningitis y sepsis. CONCLUSIONES: Enfermedad neumocócica es importante problema de salud pública en Brasil. Análisis basado en el SIH puede contribuir para la vigilancia epidemiológica de la enfermedad neumocócica y para la evaluación del impacto del programa de vacunación. OBJETIVO: Estimar as hospitalizações por doença pneumocócica com base em dados do Sistema de Informações Hospitalares (SIH). MÉTODOS: Estudo descritivo com base em dados do SIH de janeiro de 2004 a dezembro de 2006: números de hospitalizações e mortes por meningite pneumocócica, sepse pneumocócica, pneumonia pneumocócicca e Streptococcus pneumoniae como causa de doenças ocorridas no Brasil. Dados da Pesquisa Nacional por Amostras de Domicílios 2003 foram utilizados para o setor privado. Casos e mortes por meningite pneumocócica notificados no Sistema Nacional de Agravos de Notificação no mesmo período também foram analisados. RESULTADOS: A doença pneumocócica foi responsável por 34.217 hospitalizações no Sistema Único de Saúde (0,1% de todas as hospitalizações). Pneumonia pneumocócica foi responsável por 64,8% dessas hospitalizações. A distribuição das estimativas de hospitalizações segundo faixa etária mostrou curva em "U", com maior freqüência entre crianças < 1 ano (110-136,9/100.000 crianças/ano). A letalidade hospitalar foi mais alta entre idosos, e entre casos de meningite e sepse. CONCLUSÕES: Doença pneumocócica é importante problema de saúde pública no Brasil. Análise baseada no SIH pode contribuir para a vigilância epidemiológica da doença pneumocócica e para a avaliação do impacto do programa de vacinação.